Nationalism, religious violence, and hate speech in nineteenth-century Western Europe: memories of intolerance - Ramón Solans, Francisco Javier (Routledge studies in religion and politics, 2024)
"Nationalism, Religious Violence, and Hate Speech in Nineteenth-Century Western Europe critically analyzes the role played by different memories of past religious violence in public debates in nineteenth-century Europe. This book will appeal to students and scholars of politics, religious tolerance and freedom, hate speech, nationalism, religious history, and European history"--